Perspective Review: The Influence of Gait Efficacy on Improving Physical Activity in Community-Dwelling Older Adults - Nur Amalia, Riskah (Indonesian Contemporary Nursing Journal (ICON Journal), 2023)
Aging appears to be associated with a rise in the prevalence of inactivity. The Covid-19 pandemic was also reported associated with physical functioning and fall outcomes, with the greatest effect on individuals with reduced physical activity and social. Therefore, the elderly as the most populous group vulnerable need serious attention. Gait efficacy is defined as an individual’s perception of their level of confidence in order to perform safe walking tasks. Increasing older adults' gait-related self-efficacy is potentially necessary in order to promote self-regulation of physical activity and initiate the development of good physical activity habits as early prevention of disuse syndrome or inactivity in older adults.